OTHR-14. DIENCEPHALIC SYNDROME SECONDARY TO PITUITARY STALK THICKENING. (4th December 2020) - Almeida, Carlos; Mançano, Bruna Minniti; Eugui, Gilda D'Agostino; Matsushita, Marcus; Alvarenga, Gabrielle; Lourenço, Lucas Dias
Abstract: BACKGROUND: Diencephalic syndrome (DS) is a rare condition associated with neoplastic lesions of the sellar-suprasellar region, whose pathophysiological mechanisms are still unclear. DS occurs in <10% of hypothalamic gliomas and has also been described in suprasellar germinomas, craniopharyngiomas, epidermoid cysts, rarely with non-suprasellar lesions such as brainstem gliomas. DS has not been associated with isolated pituitary stalk thickening. Isolated pituitary stalk thickening (IPST) presents a diagnostic challenge, ranging from benign (craniopharyngioma) to malignant lesions (germinoma, metastasis, histiocytoses of the Langerhans group). The coexistence of diabetes insipidus (DI) with anterior pituitary dysfunction and IPST implies more risk to harbor neoplasia. CASE REPORT: A 6-year old girl presented with DI and inadequate weight gain (despite regular caloric intake) and preservation of linear growth. Neurological examination showed no abnormalities. However, physical examination revealed a malnourished patient (both weight-for-age value and body-mass-index below the third percentile). Blood tests and negative IgA anti-endomysial antibodies excluded malabsorption as a cause of her malnutrition; endocrine work-up excluded thyroid dysfunction, growth hormone deficiency, and adrenal insufficiency. Magnetic resonance imaging (MRI) showed thickening of the pituitary stalk with a transverse diameter of 7 mm. The patient underwent a biopsy through a supraorbital eyebrow approach. Histopathological examination revealed lymphocytic hypophysitis, with tissue markers all negative for germinoma. The girl is currently under follow up with serial MRI every three months. CONCLUSION: DS should be considered as a differential diagnosis in any child with failure to thrive, and imaging studies should be performed even if there are no additional neurological symptoms.